Comorbid substance use diagnoses and partner violence among offenders receiving pharmacotherapy for opioid dependence. Issue 3 (2nd July 2016) - Crane, Cory A.; Schlauch, Robert C.; Devine, Susan; Easton, Caroline J.
ABSTRACT: While previous studies find mixed evidence of an association between opioid use and intimate partner violence perpetration among community samples, initial evidence has detected increased rates of partner violence among individuals receiving pharmacological intervention for opioid dependence. The current study evaluated the role of current comorbid substance use diagnoses, a robust risk factor for violent behavior, on the likelihood of perpetrating partner violence among a high risk sample of offenders receiving pharmacological intervention for opioid dependence. The authors analyzed self-report data provided by 81 (55 male) opioid dependent offenders during a court-ordered substance use interview. Approximately one-third of the sample evidenced the recent use of intimate partner violence. Findings indicated that cocaine and benzodiazepine use were independently associated with an increased likelihood of reporting physical partner violence. Alcohol and cannabis use were not associated with partner violence. The current results offer further support for the ongoing need to conduct routine partner violence screenings among substance involved offenders and highlight the importance of developing individualized treatment plans that address comorbid substance use and partner-violent behaviors among individuals in treatment for opioid dependence.